Molecular Inhibition for Selective CO2 Conversion. (4th July 2022) - Creissen, Charles E.; Rivera de la Cruz, José Guillermo; Karapinar, Dilan; Taverna, Dario; Schreiber, Moritz W.; Fontecave, Marc
Abstract: Electrochemical CO2 reduction presents a sustainable route to the production of chemicals and fuels. Achieving a narrow product distribution with heterogeneous Cu catalysts is challenging and conventional material modifications offer limited control over selectivity. Here, we show that surface‐immobilised molecular species can act as inhibitors for specific carbon products to provide rational control over product distributions. Combined experimental and computational results showed that anchoring of a thiol‐functionalised pyridine on Cu destabilises a surface‐bound reaction intermediate to energetically block a CO‐producing pathway, thereby favouring formate production. The nitrogen atom was shown to be essential to the inhibition mechanism. The ability of molecules to control selectivity through inhibition of specific reaction pathways offers a unique approach to rationally modify heterogeneous catalysts. Abstract : Molecular modifiers can be used to alter the product selectivity of heterogeneous catalysts for electrochemical carbon dioxide reduction. In this study, immobilisation of a well‐defined pyridine species on a copper catalyst inhibits CO and C2+ product formation, enabling the selective generation of formate at high reaction rates.